Insights on the Multifunctional Activities of Magnolol. (23rd May 2019) - Zhang, Jianhong; Chen, Zhixi; Huang, Xianhua; Shi, Weimei; Zhang, Rui; Chen, Meiling; Huang, Hao; Wu, Longhuo
Abstract : Over years, various biological constituents are isolated from Traditional Chinese Medicine and confirmed to show multifunctional activities. Magnolol, a hydroxylated biphenyl natural compound isolated from Magnolia officinalis, has been extensively documented and shows a range of biological activities. Many signaling pathways include, but are not limited to, NF- κ B/MAPK, Nrf2/HO-1, and PI3K/Akt pathways, which are implicated in the biological functions mediated by magnolol. Thus, magnolol is considered as a promising therapeutic agent for clinic research. However, the low water solubility, the low bioavailability, and the rapid metabolism of magnolol dramatically limit its clinical application. In this review, we will comprehensively discuss the last five-year progress of the biological activities of magnolol, including anti-inflammatory, antimicroorganism, antioxidative, anticancer, neuroprotective, cardiovascular protection, metabolism regulation, and ion-mediating activity.